Pengembangan Buku Ajar Ilmu Pengetahuan Alam Berbasis Higher Order Thinking Skill untuk Siswa Sekolah Dasar - Maptuhah Maptuhah; Asep Saefurrohman; Wida Rachmiati (Dawuh Guru: Jurnal Pendidikan MI/SD, 2023)
The aim of this research to knowing the development procedures, feasibility and effectiveness of textbooks to improve the higher order thinking skills grade V SD/MI students. This research uses the Research and Development (R&D) research method and the research model used is the 4D model. Based on the results of the research, the development procedure is carried out referring to the 4D model which has 4 steps, namely Define, Design, Develop, and Disseminate. The results of the analysis of the validation sheets of material experts and media experts, the average score of the product is 87% (very good) and 79% (good) respectively, meaning that the product has been judged "feasible (Valid)". Based on the results of the teacher response questionnaire, the average score obtained is 80% (good) meaning that the product has been judged "feasible (Valid)". It can be concluded that textbooks are worth testing in schools. Based on the results of the textbook trial to 12 grade V students at SDN Rancalutung, students showed a positive response in participating in learning with textbooks, this can be seen from the results of the analysis of student response questionnaires, which was 100%. Then the percentage of student learning completion before using this textbook is 33% while after using this textbook it reaches a score above the school's KKM which is 92%. It can be concluded that the HOTS-based ecosystem material science textbook can effectively improve the higher order thinking skills of grade V SD/MI students.